Membentuk Nilai Agama dan Moral Melalui Film Upin Ipin dengan Analisis Semiotik - Feriska Listrianti; Fathor Rozi; Nur Sofia Salsabila (Cendekia, 2023)
This study aims to find out how the content in the upin ipin animated Ramadan strains episode can shape the religious and moral values ​​of early childhood. This research uses a qualitative approach with Roland Barthes' semiotic analysis. Data collection techniques include observation, interviews and documentation. The data analysis technique is carried out systematically, starting with data collection, semiotic analysis and drawing conclusions. The results of the study are that the animation of upin ipin episodes of Ramadan strains has seven values ​​that help form children's religious and moral values ​​including politeness, prayer and recitation, things that break fasting, increase practice in the month of Ramadan, prayer for breaking the fast and intention of fasting, saying hello, and singing the Hijriyah month. This upin ipin episode of Ramadan strains is very appropriate to be used as an example and watched by a wide audience with the hope that moral and religious values ​​can be conveyed in a simple way and can be well received by early childhood, especially parents and families. The animated film Upin Ipin episodes of Ramadhan strains deserves to be watched by all groups, young people and adults alike in the hope that the impression of religious and moral values ​​from this animation can be conveyed and well received.